Menstrual cycle-related fluctuations in oxytocin concentrations: a systematic review and meta-analysis - Engel, Sinha; Ditzen, Beate (Frontiers in neuroendocrinology, 2019)
Oxytocin affects physiological and psychological functions that are often expressed sex-specifically, suggesting interactions between oxytocin and sex hormones. As female sex hormone concentrations change during the menstrual cycle, oxytocin might fluctuate, too. This systematic review and meta-analysis investigated endogenous oxytocin concentrations across menstrual cycle phases in healthy women. Data from 13 studies (120 women) showed a significant increase of oxytocin concentrations from the early follicular phase to ovulation (g=0.39 [0.25; 0.53], p<.001) and a significant decrease from ovulation to the mid-luteal phase (g=−0.50 [−0.81; −0.18], p<.001). There were no significant differences between the early follicular and mid-luteal phase (g=−0.19 [−0.70; −0.32], p=.471). These findings contribute to a deeper understanding of differences in normal and abnormal psychobiological processes in women. They highlight the necessity to consider the menstrual cycle phase in studies on oxytocin in women.
Available online 17 November 2018
Gesehen am 09.10.2019